2020
DOI: 10.3390/ani10081399
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1-Mediated FDNCR1 Regulates Porcine Preadipocyte Differentiation via the TGF-β Signaling Pathway

Abstract: Adipocyte differentiation and lipid metabolism have important regulatory effects on the quality of meat from livestock. A variety of transcription factors regulate preadipocyte differentiation. Several studies have revealed that transforming growth factor-beta (TGF-β1) may play a key role in epithelial–mesenchymal transition (EMT); however, little is known about the effects of TGF-β1 treatment on porcine preadipocytes. To explore the role of TGF-β1 in porcine adipocyte differentiation, porcine preadipocytes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…For example, the LncRNA GAS5 inhibits lipogenesis in 3T3-L1 cells through the miR-21a-5p / PTEN signaling pathway [44]. FDNCR1 affects porcine lipogenesis by competitively binding miR-204 to regulate the TGF-β pathway [45]. However, for some pathways identi ed here, their involvement in the goat preadipocyte differentiation process is being reported for the rst time.…”
Section: Discussionmentioning
confidence: 86%
“…For example, the LncRNA GAS5 inhibits lipogenesis in 3T3-L1 cells through the miR-21a-5p / PTEN signaling pathway [44]. FDNCR1 affects porcine lipogenesis by competitively binding miR-204 to regulate the TGF-β pathway [45]. However, for some pathways identi ed here, their involvement in the goat preadipocyte differentiation process is being reported for the rst time.…”
Section: Discussionmentioning
confidence: 86%
“…The GO enrichment result showed that the mRNAs we found were all participated in macromolecule metabolic process. Three pathways, PI3K-Akt signaling pathway, AMPK signaling pathway and TGF-beta signaling pathway, got our attentions in KEGG enrichment result, cause they all having essential roles during adipocyte differentiation [ 26 , 55 , 56 ]. Then we obtained 5 key mRNAs in the circRNA-miRNA-mRNA network, FOXO3 [ 57 ], PPP2CA [ 58 ], EEIF4E [ 59 ], CDK6 [ 60 ] and ACVR1 [ 61 ], and they all showed valuable functions in fat-related research.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the LncRNA GAS5 inhibits lipogenesis in 3T3-L1 cells through the miR-21a-5p/PTEN signaling pathway ( Liu et al, 2018 ). FDNCR1 affects porcine lipogenesis by competitively binding miR-204 to regulate the TGF-β pathway ( Zhang et al, 2020 ). However, for some pathways identified here, their involvement in the goat preadipocyte differentiation process is being reported for the first time.…”
Section: Discussionmentioning
confidence: 99%